2023
DOI: 10.1001/jamanetworkopen.2023.1455
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Burden of Stroke in China in 2020

Abstract: ImportanceStroke is the leading cause of death in China. However, recent data about the up-to-date stroke burden in China are limited.ObjectiveTo investigate the urban-rural disparity of stroke burden in the Chinese adult population, including prevalence, incidence, and mortality rate, and disparities between urban and rural populations.Design, Setting, and ParticipantsThis cross-sectional study was based on a nationally representative survey that included 676 394 participants aged 40 years and older. It was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
101
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 247 publications
(103 citation statements)
references
References 38 publications
1
101
1
Order By: Relevance
“…Looking ahead, the number of stroke survivors is projected to increase by 27% by the year 2047 within the European Union (Wafa et al, 2020). In the United States, stroke remains a grave concern, with 14,000 deaths attributed to it annually, accounting for approximately one out of every 20 deaths in the country (Tu et al, 2023). China faces an especially formidable challenge in the realm of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Looking ahead, the number of stroke survivors is projected to increase by 27% by the year 2047 within the European Union (Wafa et al, 2020). In the United States, stroke remains a grave concern, with 14,000 deaths attributed to it annually, accounting for approximately one out of every 20 deaths in the country (Tu et al, 2023). China faces an especially formidable challenge in the realm of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…It is the second-leading cause of death and disability worldwide [ 4 – 6 ], with five major characteristics: high morbidity, disability, mortality, recurrence, and economic burden [ 7 ]. However, the problem of stroke is more serious and prominent in China, with a recent study showing that the overall prevalence, morbidity, and mortality of stroke among adults aged 40 years and older is estimated to be 2.6% in 2020 [ 8 ], and stroke has been classified as a major chronic noncommunicable disease in China and is the leading cause of death and disability among Chinese adults [ 7 ],Stroke has become a disaster, threatening human life, health, and quality of life [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is the second leading cause of mortality worldwide and the primary cause of disability and mortality in China (1)(2)(3). In 2020, ischemic stroke constituted 15.5 million (86.8%) of all incident stroke cases in the Chinese population aged ≥40 years (4). Hypertension is one of the leading risk factors for stroke (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, ischemic stroke constituted 15.5 million (86.8%) of all incident stroke cases in the Chinese population aged ≥40 years (4). Hypertension is one of the leading risk factors for stroke (1)(2)(3)(4). Previous studies have revealed a closer relationship between hypertension and stroke in Asian populations, especially among the Chinese, than that in the European, American, Australian, and New Zealand populations (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%